Oxidized alginate-gelatin (ADA-GEL)/silk fibroin/Cu-Ag doped mesoporous bioactive glass nanoparticle-based hydrogels for potential wound care treatments - Akhtar, Memoona; Nazneen, Arooba; Awais, Muhammad; Hussain, Rabia; Khan, Ahmad; Irfan, Muhammad; Avcu, Egemen; Ur Rehman, Muhammad Atiq; Boccaccini, Aldo R. (Biomedical Materials, 2024)
The present work focuses on developing 5% w/v oxidized alginate (alginate di aldehyde, ADA)-7.5% w/v gelatin (GEL) hydrogels incorporating 0.25% w/v silk fibroin (SF) and loaded with 0.3% w/v Cu-Ag doped mesoporous bioactive glass nanoparticles (Cu-Ag MBGNs). The microstructural, mechanical, and biological properties of the composite hydrogels were characterized in detail. The porous microstructure of the developed ADA-GEL based hydrogels was confirmed by scanning electron microscopy, while the presence of Cu-Ag MBGNs in the synthesized hydrogels was determined using energy dispersive x-ray spectroscopy. The incorporation of 0.3% w/v Cu-Ag MBGNs reduced the mechanical properties of the synthesized hydrogels, as investigated using micro-tensile testing. The synthesized ADA-GEL loaded with 0.25% w/v SF and 0.3% w/v Cu-Ag MBGNs showed a potent antibacterial effect against Escherichia coli and Staphylococcus aureus. Cellular studies using the NIH3T3-E1 fibroblast cell line confirmed that ADA-GEL films incorporated with 0.3% w/v Cu-Ag MBGNs exhibited promising cellular viability as compared to pure ADA-GEL (determined by WST-8 assay). The addition of SF improved the biocompatibility, degradation rate, moisturizing effects, and stretchability of the developed hydrogels, as determined in vitro. Such multimaterial hydrogels can stimulate angiogenesis and exhibit desirable antibacterial properties. Therefore further (in vivo) tests are justified to assess the hydrogels’ potential for wound dressing and skin tissue healing applications.
CRIS-Team Scopus Importer:2024-03-29
Keywords: alginate; antibacterial activity; biocompatibility; gelation; silk; wound healing